2012
DOI: 10.1002/sia.5077
|View full text |Cite
|
Sign up to set email alerts
|

An experimental and theoretical view of energetic C60 cluster bombardment onto molecular solids

Abstract: Recent experimental measurements and calculations performed by molecular dynamics computer simulations indicate, for highly energetic C60 primary ions bombarding molecular solids, the emission of intact molecules is unique. An energy- and angle-resolved neutral mass spectrometer coupled with laser photoionization techniques was used to measure the polar angle distribution of neutral benzo[a]pyrene molecules desorbed by 20-keV C60+ primary ions and observed to peak at off-normal angles integrated over all poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…These observations are consistent with the experimental observations reported from earlier studies on the benefits of ice matrices and water dosing of samples that resulted in increased [M + H] + yields. Furthermore, MD simulations from Garrison’s group have suggested that hydrogen species generated by a primary ion impact in the emission zone may well give rise to protonated molecules that are in a sense preformed to be sputtered out by subsequent primary particle impacts . The data presented in this paper is understandable in the light of this idea such that a water cluster impact would result in an increased density of hydrogen, protons, oxygen atoms and ions, and hydroxyl ions.…”
Section: Discussion and Conclusionmentioning
confidence: 76%
See 1 more Smart Citation
“…These observations are consistent with the experimental observations reported from earlier studies on the benefits of ice matrices and water dosing of samples that resulted in increased [M + H] + yields. Furthermore, MD simulations from Garrison’s group have suggested that hydrogen species generated by a primary ion impact in the emission zone may well give rise to protonated molecules that are in a sense preformed to be sputtered out by subsequent primary particle impacts . The data presented in this paper is understandable in the light of this idea such that a water cluster impact would result in an increased density of hydrogen, protons, oxygen atoms and ions, and hydroxyl ions.…”
Section: Discussion and Conclusionmentioning
confidence: 76%
“…Furthermore, MD simulations from Garrison’s group have suggested that hydrogen species generated by a primary ion impact in the emission zone may well give rise to protonated molecules that are in a sense preformed to be sputtered out by subsequent primary particle impacts. 32 The data presented in this paper is understandable in the light of this idea such that a water cluster impact would result in an increased density of hydrogen, protons, oxygen atoms and ions, and hydroxyl ions. The resulting ion–molecule reactions in the emission zone would be those expected to result in increased secondary ion formation and subsequent release.…”
Section: Discussion and Conclusionmentioning
confidence: 84%
“…The energy/velocity distribution of the SIs produced in SIMS is one of the key factors that determine the spatial and temporal distribution of the ions at the detector. To simulate this we used a Boltzmann distribution of initial kinetic energies (peaking at 1 eV), based on the extraction energy of sputtered gold particles and a cos 12 (θ) angular distribution based on experimental data for nickel sputtered by C 60 + . Optimizing the mass and spatial resolution of the SIMS instrument via the SIMION simulations was achieved using a mixture of two methods, a gradient search and a genetic algorithm (GA).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the shape of the angular spectra depends on a type of analyzed material and on the properties of the bombarding cluster projectiles. , For cluster ions with sizes typically used in the GCIBs, the size of the projectile and its angle of incidence on the surface have the most significant impact. For large cluster projectiles bombarding inorganic samples, the particles are ejected predominantly at large polar angles. ,, This type of sputtering is termed “lateral sputtering”.…”
mentioning
confidence: 99%